Complex Component of Oncocytic and Non-Oncocytic Lipoadenomas in the Parotid Gland: A Case Report - Fuyuki Sato; Takashi Nakajima; Takashi Sugino (Diagnostics, 2021)
Oncocytic lipoadenoma of the salivary gland is a rare tumor that develops mainly in the parotid gland. We report a case of oncocytic lipoadenoma of the parotid gland in a 70-year-old woman. The tumor measured 30 × 20 mm and had a well-circumscribed tan-brown surface. The tumor was histologically composed of oncocytic and lipomatous lesions without atypia. In addition to the oncocytic lipoadenoma, a small lipomatous tumor, measuring 10 × 7 mm, was found in the resected parotid gland. Macroscopically, this tumor was yellow and indistinguishable from the parotid gland. Microscopically, the tumor was rich in fats and contained an area of conglomerated duct-like proliferation and salivary gland components. Therefore, the tumor was diagnosed as a non-oncocytic lipoadenoma with a sialoadenoma component. We report the first case of double component oncocytic and non-oncocytic lipoadenomas of the salivary gland.